Lenalidomide, Bortezomib, Pegylated Liposomal Doxorubicin, and Dexamethasone in Newly Diagnosed Multiple Myeloma: Updated Results of Phase I/II MMRC Trial - Jakubowiak, Andrzej J.; Reece, Donna E.; Hofmeister, Craig C.; Lonial, Sagar; Zimmerman, Todd M.; Campagnaro, Erica L.; Schlossman, Robert L.; Laubach, Jacob; Raje, Noopur; Anderson, Tara; Griffith, Kent; Hill, Melissa; et al. (Blood, 2009)
Abstract 132 Background: The RVD combination of Lenalidomide (Revlimid®, Len), Bortezomib, (Velcade®, Bz), and Dexamethasone (Dex) and the VDD combination of Bz, pegylated liposomal doxorubicin (Doxil®, PLD), and Dex are among the most active in newly diagnosed multiple myeloma (MM). Pre-clinical studies suggest that combining 4 drugs from RVD and VDD into RVDD may produce even higher activity. The aims of this Phase I/II trial were to determine the maximum tolerated dose (MTD) of the RVDD regimen and to assess its safety and evaluate efficacy in newly diagnosed MM. Methods: Patients (Pts) received Len 15–25 mg (days 1–14), Bz 1.3 mg/m2 (days 1, 4, 8, 11), Dex 20/10 mg (cycles 1–4/5–8; days of and after Bz), PLD 20 or 30 mg/m2 (day 4) at 4 dose levels for up to eight 21-day cycles. In the Phase I portion of the study, pts were assigned to dose levels 1-4 according to the TITE-CRM algorithm. Responses were assessed by modified European Group for Blood and Marrow Transplantation (EBMT) and Uniform Criteria. Pts who achieved at least partial response (PR) could proceed to autologus stem cell transplant (ASCT) after ≥ 4 cycles. After 8 cycles, pts could continue treatment using 21-day maintenance cycles with Len (days 1–14), Bz (day 1 and 8), and Dex (days of and after Bz) at the doses tolerated by the end of initial treatment. Results: The study has enrolled 68 pts to date (median age 61; 52% ISS II/III), 42 pts in phase I (including 6 pts treated at the MTD) and 26 pts in phase II, for a total of 32 of 38 planned pts at the MTD. Pts received a median of 4 cycles (range 1–16); 48 completed at least 4 cycles, 11 completed all 8 cycles, and 34 have discontinued/completed therapy. Seven patients remain on maintenance therapy. Toxicity data are available for 55 pts. In the phase I, 4 pts were assigned to level 1 (Len/PLD 15/20), 11 to level 2 (Len/PLD 20/20, 21 to level 3 (Len/PLD 25/20), and 6 to level 4 (Len/PLD 25/30). Two pts were not evaluable for DLT per protocol criteria and were replaced; 1 at level 2 and 1 at level 3, leaving 40 pts evaluable for DLTs. There were no DLTs at level 1, 2 at level 2, 3 at level 3, consisting of 2 grade (G) 3 asymptomatic neutropenia on day 1 cycle 2, 1 G3 elevation of transaminases, 1 G3 drug fever, and 1 grade 3 hypophosphatemia and none at level 4. Based on the pre-determined definition of maximum tolerated dose (MTD) and probability estimates of DLTs of 4.7% for level 1, 9.7% for level 2, 13.7% for level 3, and 17.9% for level 4, the maximum planned dose level 4 was selected as the MTD for the phase II portion of the study as the closest to, but not exceeding, a target rate of 20% of DLTs. Overall, toxicities have been manageable with G3/4 toxicities in 3–18% of all pts including neutropenia (18%), thrombocytopenia (7%) , infections (16 %) , DVT (2%). There was 4% G3 and no G4 peripheral neuropathy reported, 24% G 1/2 palmar-plantar erythrodysesthesia, and no treatment-related mortality. Response rates in 57 pts evaluable for response were as follows: 96% ≥ PR, 58% ≥ VGPR, and 30% CR/nCR. In 48 pts who completed 4 cycles, defined in the protocol for efficacy assessment, response rates were: 98% ≥ PR, 58% ≥ VGPR and 29% CR/nCR; at MTD ≥PR is 100%. Response rates were not statistically different in a subset of pts (24) with 13q deletion or t(4;14) or t(14;16) or 17p del, with PR, VGPR, and CR/nCR rates 92%, 67%, and 33%, respectively. Twenty four pts proceeded to stem cell collection with 7.5 × 106 CD34+ cells/kg collected after a median of 4 cycles of RVDD (range 3–10). After a median of 6 months of follow-up, median progresssion-free survival and overall survival have not been reached. Conclusion: RVDD is well tolerated in newly diagnosed MM and appears highly active with ≥ PR of 96%, including 58% ≥VGPR, which is unaffected by adverse cytogenetic status. Pts treated at the MTD ,which was determined as Len 25 mg, Bz 1.3 mg/m2, Dex 20 mg, and PLD 30 mg/m2, and completed at least 4 cycles, show 100% ≥PR. Stem cell mobilization and collection was successful in all pts, with unremarkable transplant course reported to date. Updated toxicity and efficacy data will be presented at the meeting. Jakubowiak:Bristol Myers-Squibb: Consultancy, Honoraria, Membership on an entity's Board of Directors or advisory committees; Exelixis: Consultancy, Honoraria, Membership on an entity's Board of Directors or advisory committees; Centocor OrthoBiotech: Consultancy, Honoraria, Speakers Bureau; Celgene: Consultancy, Honoraria, Speakers Bureau; Millennium: Consultancy, Honoraria, Membership on an entity's Board of Directors or advisory committees, Speakers Bureau. Off Label Use: Lenalidomide for newly diagnosed multiple myeloma. Reece:Ortho Biotech: Honoraria, Research Funding. Lonial:Novartis: Consultancy; Gloucester: Research Funding; Bristol Myers - Squibb : Consultancy; Millennium: Consultancy, Research Funding; Celgene: Consultancy. Zimmerman:Celgene: Speakers Bureau; Millennium: Speakers Bureau; Centocor: Speakers Bureau. Schlossman:Millennium: Speakers Bureau; Celgene: Speakers Bureau. Laubach:Novartis: Advisory Board. Raje:Celgene, Norvartis, Astrazeneca: Research Funding. Anderson:Millennium: Honoraria, Speakers Bureau; Celgene: Honoraria, Speakers Bureau. Barrickman:Celgene: Employment, Equity Ownership. Tendler:Johnson and Johnson: Employment, Equity Ownership. Esseltine:Johnson and Johnson: Equity Ownership; Milllennium: Employment, Equity Ownership. Kelley:Bristol-Myers Squibb: Equity Ownership. Anderson:Millennium: Consultancy, Honoraria, Research Funding; Novartis: Consultancy, Honoraria, Research Funding; Celgene: Consultancy, Honoraria, Research Funding. Richardson:Bristol Myers-Squibb: Consultancy, Membership on an entity's Board of Directors or advisory committees, Research Funding, Speakers Bureau; Novartis: Membership on an entity's Board of Directors or advisory committees, Speakers Bureau; Celgene: Consultancy, Membership on an entity's Board of Directors or advisory committees, Speakers Bureau; Keryx: Membership on an entity's Board of Directors or advisory committees, Speakers Bureau; BMS: Membership on an entity's Board of Directors or advisory committees, Speakers Bureau; Johnson and Johnson: Membership on an entity's Board of Directors or advisory committees, Speakers Bureau.